Ethics and Professional Responsibilities of Judges in Carrying Out Duties in Law Enforcement - Yeti Kurniati; Yuninda Dwi Kartika; Yoga Gustiadi; Gede Indra Udayana; Andhika Nugraha Bhakti Agung (Civiliza Publishing, 2026)
The Judicial Code of Ethics serves as the ethical principles of judges, serving as the basis or guideline for every decision-making process in legal cases before them, as law enforcement officers, and in addressing the challenges of legal issues and legal developments. The purpose of this article is to provide the wider public with knowledge and understanding regarding ethics as a guideline and the challenges faced by judges in examining, adjudicating, and deciding legal cases. This article was written using literature and secondary data. The approach used in this research is the statutory approach. Judges are functional and state officials authorized to examine, adjudicate, and decide legal cases fairly and based on the law. Judges are responsible for interpreting and applying applicable law to cases before them and ensuring that justice and truth are achieved. The Judicial Code of Ethics is a written rule or code of conduct that judges must adhere to in carrying out their duties to ensure integrity, fairness, and public trust in the judicial institution. The Code of Ethics for the Judges' Professionalism contains the obligation and requirement to carry out their profession responsibly for the results and impacts of their actions and to refrain from violating the rights of others. The Code of Ethics is not law, but rather a norm that serves as a benchmark for legal professionals in upholding the authority of the law with humanity and justice. (Drs. H. Wildan Suyuthi Mustofa,